Torture spaces of the dictatorship’s as a biopolitical camp - Simões, Paloma Sá Souza (2021)
The article intends to analyze the concept of the state of exception developed by the Italian philosopher Giorgio Agamben, its developments, such as the idea of ??the countryside, naked life and the force of law and to relate them to the Brazilian historical-political context of the military dictatorship. It has, then, as a general hypothesis that the torture spaces that worked at the time are the biopolitical camps that emerged from the consolidation of the military regime as a state of permanent exception. From the research it was possible to verify that the military dictatorship established in the country used legislative and legal mechanisms to give the state of exception a legal veneer through the Institutional Acts (AI) edited by the military, which coincide with the conception of the force of law developed by Agamben, still, that the spaces of torture used during the period of the military regime fit in the notion of biopolitical camp developed by the agambenian theory. Keywords: Military dictatorship. State of exception. Camp. Biopolitics. Force of law.